HUBUNGAN ANTARA BERAT JENIS DAN INTENSITAS SERANGAN PENGGEREK KAYU DI LAUT TERHADAP BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Mohammad Muslich; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1989)
Many factors determine the susceptibility of wood to marine borer attack. It is thought that one of them is the specific gravity.A study on the relationship between wood specific gravity and the intensity of marine borer attack was conducted in the seashore of Rambut Island (in Java Sea) in 1988. Samples were made of woods of industrial plantation forest species with the size of 30 cm long, 5 cm wide and 2,5 cm high. The samples were randomly arranged like a raft and put inside the sea. They were observed after three months.The results reveal that specific gravity asertain the intensity of marine borer infestation, except Tectona grandis, Tectona grandis 12 the most resistant to marine borer attack although its specific gravity is lower than Eucalyptus urophylla, Altingia excelsa, Acacia mangium and Pometia pinnata.